Patterns of genetic divergence in the Ilyodromus amplicolis lineage (Crustacea, Ostracoda), with descriptions of three new species - Shearn, Rylan; Schön, Isa; Martens, Koen; Halse, Stuart; Krawiec, Joe; Koenders, Annette (Zootaxa, 2017)
In this study, 13 previously recorded populations of Ilyodromus amplicolis De Deckker, 1981 from temporary aquatic habitats in Western Australia were scanned for undescribed species diversity using morphological and molecular systematics techniques. The study found congruent morphological and molecular evidence for three species that are new to science, all of which are formally described here (I. armacutis n. sp., I. sensaddito n. sp. and I. hiatus n. sp.). The findings shed light on the potential for further undescribed diversity in the genus Ilyodromus Sars, 1894.